Arctiin Alleviates Atopic Dermatitis Against Inflammation and Pyroptosis Through Suppressing TLR4/MyD88/NF-κB and NLRP3/Caspase-1/GSDMD Signaling Pathways - Li J; Du X; Mu Z; Han X (Dove Medical Press, 2024)
Jingmin Li,1,2 Xuefei Du,1 Zhenzhen Mu,1 Xiuping Han1 1Department of Dermatology, Shengjing Hospital, China Medical University, Shenyang, Liaoning, People's Republic of China; 2Department of Dermatology, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Tongji Shanxi Hospital, Taiyuan, People's Republic of ChinaCorrespondence: Xiuping Han, Department of Dermatology, Shengjing Hospital, China Medical University, Shenyang, People's Republic of China, Tel + 86 18940251646, Email hanxiuping66@126.comPurpose: Atopic dermatitis (AD) is a prevalent skin condition worldwide. The immune response plays a crucial role in the pathogenesis of AD. Arctiin (ARC), a natural lignan, has been extensively investigated because of its anti-inflammatory, antioxidant, and anticancer properties. However, the impact of ARC on AD remains uncertain. Therefore, this study investigated the therapeutic effects of ARC in AD.Methods: AD-like lesions were induced in mice by applying 2,4-dinitrochlorobenzene (DNCB). The efficacy of ARC in AD was assessed by measuring skin lesion scores and thickness, pathological observation, and serum IgE concentrations. The expression of relevant proteins and genes in the back skin of the mice was assessed. Moreover, the TLR4/MyD88/NF-κB and NLRP3/Caspase-1/GSDMD signaling pathways were assessed in HaCaT cells stimulated with TNF-α and IFN-γ.Results: ARC effectively alleviated AD-like dermatitis induced by DNCB in mice, reducing the skin thickness, mast cell infiltration in skin tissue, and serum total IgE levels. In addition, the expression of IL-1β and the mRNA transcription of TSLP and IFN-γ were downregulated. ARC also suppressed the TLR4/MyD88/NF-κB pathway, and molecular docking confirmed that ARC had exceptional binding properties with TLR4. Moreover, ARC ameliorated pyroptosis by inhibiting the activation of the nod-like receptor protein-3/Caspase-1/GSDMD cascade.Conclusion: ARC has remarkable anti-AD effects by inhibiting inflammation and pyroptosis through the TLR4/MyD88/NF-κB and NLRP3/Caspase-1/GSDMD signaling pathways. This suggests that ARC has potential as a new drug candidate for treating AD, which provides a novel approach to the clinical management of AD. Keywords: arctiin, atopic dermatitis, inflammation, pyroptosis